The interplay between national culture and diffusion of activitybased costing: an Asia-Pacific perspective / Bülend Terzioglu and Elsie S. K. Chan - Bülend, Terzioglu; Chan, Elsie S. K. (2014)
This paper provides an updated overview of the state of activity-based costing (ABC) and time-driven activity-based costing (TDABC) research in selected Asia Pacific countries and describes the association between national culture and ABC implementation. We reviewed literature on ABC and TDABC relating to selected Asia Pacific countries from 42 academic and professional journals published in the period 1987-2012. Our findings show substantial divergence in ABC implementation rates. In this study, we have not identified any research on TDABC in Asia Pacific countries that has been published. Opportunities exist for more extensive studies of ABC and TDABC that take account of Asia Pacific national cultures.